Risk Factors For Unintentional Childhood Poisoning - Rahma, S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Objectives:   To   identify   child  or  family  related  risk  factors   forunintentional childhood  poisoning in Sulaymaniyah, Iraq  and to suggestpossible causes and preventive measures.Methods: This is an epidemiological description and a case-control study. The study was undertaken in Sulaymani ,in 2004-2005. Cases were 200 children who were admitted to the hospital for treatment of poisoning. For every case two controls  were selected. Al l   parents of the children were interviewed  by  using a  questionnaire  that  incl uded  demographic  and poisoning characteristic information.Results: Kerosene poisoning was more  common among children (60%)and most poison ing occurred inside the home (88%).Boys (65%), and children aged 1-5 years (79%) had most poisoning thanothers. Tn  75% of cases,  poisonous products were accessible. Children without adult supervision and those with previous poisoning were at increased risk of poisoning (P